Addition of Alkali Activator and Substitution of GGBFS in Hydraulic Cement for High Early Flexural Strength and High Slump Concrete - Maria Apolonia Palan Keron; Iman Satyarno; Suprapto Siswosukarto; Ratna Dwiyani Nawangsasi; Muhammad Hasan Taufiq (Universitas Negeri Yogyakarta, 2026)
To lower CO2 emissions, the construction sector is increasingly adopting sustainable practices, such as cutting back on clinker usage in cement manufacturing. Hydraulic cement is an environmentally friendly cement material because it uses a smaller amount of clinker. The amount of industrial waste, including materials like Ground Granulated Blast Furnace Slag (GGBFS), keeps rising each year. Because of this, it is frequently used as an alternative to cement. However, concrete with GGBFS substitution generally experiences a delay in early strength development due to its low reactivity to water. To overcome this, adding an alkali activator in NaOH and Na2SiO3 is necessary. In this study, the dosage of alkali activator was varied at 0%, 2.5%, 5% and 7.5% by weight of GGBFS with R and A values set at 1.5 and 0.45. In addition, using GGBFS can also reduce the workability of concrete, so it is necessary to use a superplasticizer in the form of Sika® Viscocrete®-1050 to improve concrete flow properties. The dosage of superplasticizer used was 0.75% by weight with a target slump of 20 cm for ease of working. The amount of GGBFS used was 30% by weight. To evaluate the materials performance, test were carried out to measure the concrete workability, compressive strength of paste and concrete flexural strength after 3 days of curing. The results show that increasing the dosage of alkali activator can increase the paste compressive strength by more than 24 MPa according to the requirements of using hydraulic cement and concrete flexural strength by more than 3 MPa in 3 days. Concrete with a 7.5% alkali activator dosage can achieve a concrete flexural strength of 4.81 MPa at 3 days and has a slump value of 20 cm. This research can be a solution to reduce CO2 emissions and is useful for construction projects that require high flexural strength values at early ages and high slump.